Examining the Carbon Footprint of Conferences with an Emphasis on Energy Consumption and Catering - Viktoria Mannheim; Judit Lovasné Avató (Energies)
This research study presents a comparison of an in-person and an online conference in terms of environmental impact and energy efficiency. The main goal of our research was to prepare a complete life cycle assessment of a two-day (15-h), 200-participant in-person and online conference based on different impact assessment methods. Life cycle assessments focus on the numerical determination of the decarbonization of conference consumption (lunch, dinner, food and beverage consumption during breaks), conference organization (discussions, correspondence, abstract booklet, registration package), travel, and infrastructure. The meals were examined by connecting the stages of preparation, cooking, consumption and end-of-life cycle as a cradle-to-grave analysis. We paid particular attention to the calculation of energy consumption. After carbon footprint comparisons, the areas with the highest impacts with pie diagrams were identified. Lastly, a SWOT chart and an SAP-LAP analysis diagram summarize the achievable objectives and challenges. In conclusion, there is no outstanding difference between the impact assessment methods for the carbon footprint investigation. Travel contributes 57% of the overall carbon footprint at in-person conferences, while the environmental impact of meals holds the second largest share, at 8.41 kg CO2 equivalent/person/hour. Excluding meals and travel, the calculated carbon footprint is 0.362 kg CO2 equivalent/person/hour (only considering the effect of preparation, organization, administration and registration package). Our initial hypothesis was that an online conference reduces decarbonization, which the results confirm.